Ensino colaborativo como estratégia de formação continuada de professores para favorecer a inclusão escolar - Rabelo, Lucélia Cardoso Cavalcante (2012)
This study approaches the thematic of the collaborative teaching, which is understood as a partnership between teachers of regular classes and special education teachers who share responsibilities, as well as the whole process of planning, instructing and evaluating the procedures involved in teaching students with special education needs. The experiences of collaborative teaching have facilitated the inclusion of students with special needs in regular schools and at the same time it has contributed to the continuous formation of teachers. In this context, this study investigated if collaborative teaching can enable teacher´s continuous formation and support the school inclusion of students with autism. This research intended to analyze the contributions and limitations of the collaborative teaching experience to the continuous formation of teachers who belong either to regular or to special education system. The research has been developed in a qualitative approach, based on the collaborative research model. The researcher, two teachers from regular classes and one trainee, who taught the second and third grades of an Elementary regular school and five special education teachers that taught three students with autism have taken part of this study . The study took place in three public elementary schools in the state of Pará. The following instruments were used to collect data: questionnaires, a form containing student´s personal information, two scripts to guide the group meetings; participative observations sections during regular and special education classes which were registered in a field diary. As part of the collaborative teaching process, the researcher has coordinated eight meetings with all the teachers (these meetings have been recorded), twenty meetings with each teacher to plan, execute and evaluate the activities prepared to the students and twenty eight meetings involving the teachers and their students with special needs. A focal group technique was applied to the group of teachers in two meetings. The data were organized and analyzed according to a category system. The results have showed that collaborative teaching in fact enables the continuous formation of the teachers who participated in this study. It has also supported the inclusion of students with autism in regular classes. Nevertheless, it´s important to warn that collaborative teaching can`t supply all demands from teachers in regular and special education schools. We hope the collaborative teaching may be recognized as an effective strategy that can be part of policies which aim to create an inclusive education system in Brazil.